Cost-effectiveness analysis of pharmacokinetic-driven prophylaxis vs. standard prophylaxis in patients with severe haemophilia A. Issue 6 (September 2017) - Iannazzo, Sergio; Cortesi, Paolo A.; Crea, Roberto; Steinitz, Katharina; Mantovani, Lorenzo G.; Gringeri, Alessandro
Abstract : N/A: The objective of this study was to assess the cost-effectiveness of pharmacokinetic-driven prophylaxis in severe haemophilia A patients. A microsimulation model was developed to evaluate the cost-effectiveness of pharmacokinetic-driven prophylaxis vs. standard prophylaxis and estimate cost, annual joint bleed rate (AJBR), and incremental cost-effectiveness ratio over a 1-year time horizon for a hypothetical population of 10 000 severe haemophilia A patients. A dose of 30 IU/kg per 48 h was assumed for standard prophylaxis. Pharmacokinetic prophylaxis was individually adjusted to maintain trough levels at least 1 and 5 IU/dl or less. AJBR was estimated on the relationship between factor VIII (FVIII) levels and bleeding rate reported in the literature. Sensitivity analyses were performed to assess the stability of the model and the reliability of results. The FVIII dose was reduced in the 27.8% of patients with a trough level more than 5 IU/dl on standard prophylaxis, with a negligible impact on AJBR (+0.1 bleed/year). The FVIII dose was increased in the 10.6% of patients with trough levels less than 1 IU/dl on standard prophylaxis, with a significant reduction of AJBR (−1.9 bleeds/year). On average, overall, pharmacokinetic-driven prophylaxis was shown to decrease the AJBR from 1.012 to 0.845 with a slight reduction of the infusion dose of 0.36 IU/kg, with total saving of 5 197[Euro sign] per patient-year. Pharmacokinetic-driven prophylaxis was preferable (i.e. more effective and less costly) compared with standard prophylaxis, with savings of 31 205[Euro sign] per bleed avoided. Pharmacokinetic-driven prophylaxis, accounting for patients' individual pharmacokinetic variability, appears to be a promising strategy to improve outcomes with efficient use of available resources in severe haemophilia A patients.